Primary Bone Lymphoma - Elli, M.; Çelik, Hüseyin; Daǧdemir, A.; Dabak, N.; Selçuk, M.B.; Canbaz, F.C.; Kandemír, B. (My University, 2012)
Primary bone lymphoma is a rare malignancy of the bones. Diffuse large B-cell lymphoma is by far the most common histology presenting as primary bone lymphoma. We presented a 16-years old child with diffuse large B-cell lymphoma on distal femur. He was treated with systemic chemotherapy. © 2012 OMU.
Birincil Kemik Lenfomasi
Keywords: Chemotherapy; Childhood; Diffuse Large B-Cell Lymphoma; Femur; PET/CT; Primary Bone Tumor